Postzygotic barriers isolate sympatric species of Cyrtandra (Gesneriaceae) in Hawaiian montane forest understories. Issue 11 (5th November 2015) - Johnson, Melissa A.; Price, Donald K.; Price, Jonathan P.; Stacy, Elizabeth A.
Abstract : PREMISE OF THE STUDY: Recent reviews of reproductive isolation (RI) in plants propose that boundaries between closely related species are maintained predominantly through prezygotic mechanisms. However, few experimental studies have explored how boundaries are maintained in long‐lived species. Hawaiian Cyrtandra presents an intriguing challenge to our understanding of RI, as it comprises 60 shrub or small tree species that are almost exclusively restricted to wet forests, where sympatry of multiple species is common. METHODS: We assessed the relative strengths of pre‐ and postzygotic barriers among four species of Cyrtandra occurring at the extremes of the main Hawaiian Island's natural island‐age gradient, Kaua'i (4.7 Myr) and Hawai'i Island (0.6 Myr), to contrast the strengths and stages of reproductive isolation among species at different stages of divergence. KEY RESULTS: A combination of F1 seed germination, F1 seedling survival, and F1 seedling growth isolated (61–91%) three of the species from sympatric relatives. In contrast, the fourth species was isolated (59%) from its sympatric relative through phenological differences alone. Significant postzygotic barriers in between‐island crosses were also observed in one species. CONCLUSIONS: Results suggest that boundaries between sympatric Cyrtandra species in Hawaii are maintained predominantly through postzygotic barriers. Observations from between‐island crosses indicate that postzygotic barriers can arise in allopatry, which may be important in the initial divergence of populations. Future studies of RI in Cyrtandra should include a broader range of species to determine if postzygotic isolating barriers are foremost in the maintenance of species boundaries in this large genus.